In vitro evaluation of an adaptive Starling‐like controller for dual rotary ventricular assist devices. Issue 11 (25th July 2019) - Stephens, Andrew; Gregory, Shaun; Tansley, Geoff; Busch, Andrew; Salamonsen, Robert
Abstract: Rotary ventricular assist devices (VADs) operated clinically under constant speed control (CSC) cannot respond adequately to changes in patient cardiac demand, resulting in sub‐optimal VAD flow regulation. Starling‐like control (SLC) of VADs mimics the healthy ventricular flow regulation and automatically adjusts VAD speed to meet varying patient cardiac demand. The use of a fixed control line (CL – the relationship between ventricular preload and VAD flow) limits the flow regulating capability of the controller, especially in the case of exercise. Adaptive SLC (ASLC) overcomes this limitation by allowing the controller to adapt the CL to meet a diverse range of circulatory conditions. This study evaluated ASLC, SLC and CSC in a biventricular supported mock circulation loop under the simulated conditions of exercise, sleep, fluid loading and systemic hypertension. Each controller was evaluated on its ability to remain within predefined limits of VAD flow, preload, and afterload. The ASLC produced superior cardiac output (CO) during exercise (10.1 L/min) compared to SLC (7.3 L/min) and CSC (6.3 L/min). The ASLC produced favourable haemodynamics during sleep, fluid loading and systemic hypertension and could remain within a predefined haemodynamic range in three out of four simulations, suggesting improved haemodynamic performance over SLC and CSC.